Public Relations for the New Europe - Morris, Trevor; Goldsworthy, Simon; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2008)
This book is essential for anyone interested in Public Relations in New Europe Whether you are working in PR, studying PR, a journalist dealing with PR, or just interested in this fascinating and fast growing market, this book offers readers a vital insight into how PR works.
Keywords: International business enterprises; Marketing; Public relations; Industries; International economics; International Business; Marketing; Corporate Communication/Public Relations; Industries; International Economics